Sustainable reputation of lithium-ion battery supplier and its impact on transaction equilibrium in the electric vehicle supply chain - Yuan Liu; Yunqi Li; Jingjing Hao; Lingxuan Sun (Chinese Journal of Population, Resources and Environment)
In the lithium-ion battery (LIB) supply-chain, transactions involve several rounds of ordering, production and delivery between LIB suppliers and electric vehicle (EV) manufacturers. The sustainable performance of LIB suppliers, related to various characteristics, significantly affects the participants’ sustainable reputations. The EV-LIB supply-chain transaction mechanism is explored from the perspective of the exchange economy comprehensively addressing both short-term economic profit and long-term sustainable reputation. Specifically, a “profit-reputation” utility function is proposed to reflect participants’ expectations regarding cooperation profit and sustainable reputation. Additionally, an Edgeworth box model is developed to describe the participant’s balance determinations as a contract curve, revealing the Pareto conditions for mutually beneficial transactions based on sustainable performance. Furthermore, several principal-agent models are established to analyze the equilibrium of sustainable transactions within the EV-LIB supply-chain under varying dominance scenarios. A case study of an EV-LIB transaction is conducted to demonstrate the feasibility and effectiveness. This study aims to assist supply chain managers, researchers and decision-makers in exploring the role of participant’s sustainable reputation and its influence on supply-chain transaction and equilibrium, particularly in the context of designing cooperative contracts and negotiation process to foster sustainable supply chains.